Considerations on the consequences of stresses related to the challenges of professional and private life - Pruszyński, Jacek; Pruszyńska, Irena; Włodarczyk -Pruszyńska, Inga (Journal of Education, Health and Sport, 2022)
There is a group of people for whom work is an important factor in building their self-esteem. Often, such people include workers from the group of “supportive” professions, which promote behaviours that increase the risk of addiction to work. The factors contributing to this are the constant rush along with the individual tendency for perpetual self-control and meticulous checking of each performed activity. People who are idealistic about their duties, set the bar high, take too much responsibility and at the same time have low self-esteem, fall into the trap of addiction more often. The inability to independently regulate the time of their work means that they are driven by a constant internal compulsion to perform work and to think about it, combined with the accompanying feeling of discomfort in situations when the ability to deal with matters related to work is limited. Burnout can be seen as a compensatory symptom that occurs when recognition and approval are not present in a person’s life, and low self-esteem leads to an unrealistic pursuit of excellence, recognition and acceptance. A noticeable tell of burnout is the loss of features that usually characterize a person involved in their activities such as creativity, conscientious fulfilment of obligations, willingness to cooperate with others, communication skills, the ability to deal with stressful events and the ability to make independent decisions. The abovementioned skills are disrupted as a result of a number of mental, physical and behavioural changes associated with the burnout syndrome. Recovering from addiction requires complex therapy, improvement of interpersonal relationships and creation of an appropriate environment for functioning in professional and personal life.